ESTRAGON (Artemisia dracunculys L.) - Yu. P. Shevchenko (Овощи России, 2015)
Data of presented varieties and distribution of estragon crop are described. Morphological characteristics, biochemical composition, health giving qualities, and nutrition value are presented. The problems of seed multiplication, growing, yield, and harvest of this crop are discussed.